Proceedings of the 18th International Conference on World Wide Web 2009
DOI: 10.1145/1526709.1526923
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing web-based video sharing workloads

Abstract: Video sharing services that allow ordinary Web users to upload video clips of their choice and watch video clips uploaded by others have recently become very popular. This paper identifies invariants in video sharing workloads, through comparison of the workload characteristics of four popular video sharing services. Our traces contain meta-data on approximately 1.8 million videos which together have been viewed approximately 6 billion times. Using these traces, we study the similarities and differences in use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…Studies have examined the characteristics of user-generated video files [6,7,11,16,21], use of social networking features in video-sharing services [13,16], the structure of YouTube's "friend" network [15], the use of the "video response" feature of YouTube [4], the popularity characteristics of user-generated videos [5,6,10,11,16,21], and also models for user-generated video popularity prediction [14,19]. Here, we restrict attention mostly to related work on popularity characterization and modelling for user-generated videos.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have examined the characteristics of user-generated video files [6,7,11,16,21], use of social networking features in video-sharing services [13,16], the structure of YouTube's "friend" network [15], the use of the "video response" feature of YouTube [4], the popularity characteristics of user-generated videos [5,6,10,11,16,21], and also models for user-generated video popularity prediction [14,19]. Here, we restrict attention mostly to related work on popularity characterization and modelling for user-generated videos.…”
Section: Related Workmentioning
confidence: 99%
“…Prior work on user-generated video popularity characterization has typically relied either on network traffic traces from a network gateway [11,21] or meta-data sampled from video sharing services [5,6,10,16]. Both Gill et al [11,12] and Zink et al [21] analyzed YouTube video requests from a campus network and observed that the video requests follow a Zipf-like distribution and network bandwidth savings may be feasible if large proxy caches are used.…”
Section: Related Workmentioning
confidence: 99%
“…As in our steady-state experiments, we use two scenarios: one with purely random file requests, in which the popular file is requested with higher probability than the less popular ones, and one in which the files requested by each node are statically assigned. The results for both cases are similar, and for the purpose of evaluation, only results for (1) actual (2) max (3)(4)(5)(6)(7)(8)(9)(10) mean (3)(4)(5)(6)(7)(8)(9)(10) min (3)(4)(5)(6)(7)(8)(9)(10) Fig. 7: Number of active downloaders of each file type, using the random bundling policy for the dynamic experiments.…”
Section: F Dynamic Transient Experimentsmentioning
confidence: 74%
“…Characterization studies of file popularity [1]- [5] have shown that there typically is a long tail of mildly and less popular content. Companies like Amazon (books) and Apple (music) have leveraged this long tail of niche content to increase sales of more popular items as well.…”
Section: Introductionmentioning
confidence: 99%
“…As time passes, it will be able to more accurately estimate values for these parameters, allowing it to iteratively improve the solution using the subsequent steps of the algorithm. The modelling and prediction of popularity distribution curves of multimedia services has been an active research topic for several years [38,39]. Existing methods can thus be applied to estimate the cumulative popularity distribution.…”
Section: Input Parameter Estimationmentioning
confidence: 99%